(untitled) (GYMNASIUM, 2008)
The study aims to be an alternative of the selection system for the investigated value level. Through the tests system on applied criteria it is aimed finding out those structural and psychic qualities which allow the sportsman to perform efficaciously especially under competition conditions. The necessity of an alternative is also required by the different conditions under which it is performed.